Perbandingan Kualitas Hidup Pasien yang Menjalani Hemodialisis dengan Terapi Epoetin Alfa dan Epoetin Beta di RS PKU Muhammadiyah Yogyakarta - Murtisiwi, Lusia; Murti Andayani , Tri; Yuniarti, Endang (Jurnal Farmasi (Journal of Pharmacy), 2015)
In patients with chronic kidney disease who undergo hemodialysis are anemic. Anemia in chronic kidney disease (CKD) can be treated by administration of epoetin. Quality of life is an important aspect evaluated as outcomes of intervention in hemodialysis patients. This study aims to determine differences in the quality of life for patients undergoing hemodialysis therapy with epoetin alfa and epoetin beta in PKU Muhammadiyah Yogyakarta Hospital. Cross-sectional study on regular hemodialysis patients in PKU Muhammadiyah Yogyakarta Hospital was conducted in November 2014- January 2015. Assessment of the quality of life of patients using questionnaires KDQOL-SF version 1.3. The subjects of this study consisted of two groups, the first group of patients using epoetin alfa for treatment anemia, while the second group is patients taking epoetin beta therapy for the treatment of anemia. Data were analyzed using Levene test, Chi-Square Goodness of Fit, Independent t-test, Mann-Whitney test and ANCOVA. The results showed that in general the overall quality of life for patients undergoing hemodialysis therapy with epoetin alfa and epoetin beta in RS PKU Muhammadiyah Yogyakarta showed different results was not significant (p> 0.05) in the amount of 60.25 ± 12.97, group epoetin alfa and 63.93 ± 15.53 in the epoetin beta group.